Gamma-Ray Attenuation to Evaluate Soil Porosity: An Analysis of Methods - Luiz F. Pires; André B. Pereira (The Scientific World Journal)
Soil porosity (ϕ) is of a great deal for environmental studies due to the fact that water infiltrates and suffers redistribution in the soil pore space. Many physical and biochemical processes related to environmental quality occur in the soil porous system. Representative determinations of ϕ are necessary due to the importance of this physical property in several fields of natural sciences. In the current work, two methods to evaluate ϕ were analyzed by means of gamma-ray attenuation technique. The first method uses the soil attenuation approach through dry soil and saturated samples, whereas the second one utilizes the same approach but taking into account dry soil samples to assess soil bulk density and soil particle density to determine ϕ. The results obtained point out a good correlation between both methods. However, when ϕ is obtained through soil water content at saturation and a 4 mm collimator is used to collimate the gamma-ray beam the first method also shows good correlations with the traditional one.